AN ESTHETICS AND THE AGING PROCESS: THE ROLE OF THE HEALTHCARE PROFESSIONAL WHEN LOOKING FOR AESTHETIC PROCEDURES DURING OLD AGE - Gomes Valle Oliveira, Lívia (Health and Society, 2022)
Aging is a matter of prime importance, because whether due to genetic inheritance or bone structure some people age better than others. The search for quality of life, aesthetics, and self-care grows every day along with the increase in life expectancy. Elderly people looking to age healthy and with a body and skin that bring satisfaction and self-esteem are increasingly looking for aesthetic procedures. Thus, the present work aims to reflect on the role of the health professional in the search for aesthetic procedures during old age. For this, a narrative literature review was carried out. It appears that improvements in basic sanitation, health, and technological innovations, currently, there is a change in the population pyramid, with the growth of the elderly population (60 years and over) through an increase in life expectancy and a reduction in birth rates. The aging process, even though it is natural and inevitable, causes a decrease in self-confidence and acceptance, which generates a greater search for improvements in self-esteem, quality of life and self-care. In this way, the search for aesthetic procedures by the elderly has been growing and health professionals are of fundamental importance in promoting self-care, reducing stress, increasing self-esteem and quality of life of these subjects. Therefore, it is essential for these professionals to understand the subject in an integral way so that they can assess the real needs of the procedures and their real objectives, so that their identity remains preserved and their aging process is of quality and happy.